“To see oursels as others see us!” (Concept: The Journal of Contemporary Community Education Practice Theory, 2024)
In April 2025 there will, I hope, be celebrations across Scotland and beyond to mark the fiftieth anniversary of the Alexander report, the Challenge of Change and five decades of community education practice.  I shall certainly be raising a glass to a man and a publication that put Scottish community education on the map, not just of Scotland, but internationally. This article traces some of the international influence of the Scottish approach that emerged since the report was published, and in particular of its association with the wider field of community development.  I have too often felt that Scots at home, not least policy makers, have not recognised the influence Scottish practice and scholarship has had internationally. In my view, it has been and remains, huge.  I hope this article will remind readers of that. And if it reaches the eyes of Scottish policy makers and funders, that they enhance investment in this vitally important work as part of any strategy to support communities to address the challenges of change.